A Nano-Pharmaceutical Formula of Quercetin Protects from Cardiovascular Complications Associated with Metabolic Syndrome - Ahmed, Osama A. A.; Hassan, Noura A.; Azhar, Ahmad S.; El-Mas, Mahmoud M.; El-Bassossy, Hany M. (Frontiers in Pharmacology, 2021)
We recently developed a nano-preparation of the flavonoid quercetin in a self-nanoemulsifying drug delivery system (SNEDDS) with a considerably higher bioavailability compared with the standard quercetin suspension. Here, we investigated whether the quercetin loaded SNEDDS could offer better protection compared with the standard formulation against cardiovascular complications of metabolic syndrome (MetS) in rats. MetS was induced by high fructose and salt diet for 12 weeks while the nano-preparation or the standard suspension of quercetin was orally administered for the last 6 weeks. Compared to no or little effect for the standard quercetin suspension, the treatment of MetS rats with the quercetin loaded SNEDDS fully restored the depressant effect of MetS on contractility index and rate of rise in left ventricular pressure (dP/dtmax). Likewise, the prolongation by MetS of electrocardiographic markers of arrhythmogenesis (QTc, JT, and Tpeak-to-Tend intervals) and concomitant rises in dicrotic notch pressure were preferentially reversed by quercetin nano-preparation. On the other hand, the rises in the isovolumic relaxation constant (Tau, denotes diastolic dysfunction), blood pressure, pulse pressure, and difference between systolic and dicrotic pressure (SDP difference) were equally improved by the two preparations of quercetin. Additionally, no differences were noted in the ability of the two quercetin preparations in abrogating the elevated oxidative (MDA) and inflammatory (TNFα) markers in cardiac tissues of MetS rats. Histopathologically, microscopical signs of necrosis, inflammatory cell infiltration, and vascular congestion in MetS hearts were more markedly inhibited by the nano-preparation, compared with the standard preparation, of quercetin. In conclusion, the quercetin loaded SNEDDS is evidently more advantageous than the standard preparation of the drug in alleviating functional and histopathological manifestations of cardiac damage incited by MetS.